An Exploration of Public Perceptions of Illegal Immigration in South Africa: Attitudes, Influences, and Crime-Immigration - Tshimangadzo Oscar MAGADZE; Mmbengeni Victor NETSHIDZIVHANI (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study explored public perceptions of illegal immigration in South Africa, focusing on attitudes, influencing factors, and the relationship between immigration and crime. To realise this purpose, a quantitative research approach was employed, and a cross-sectional survey was conducted among 490 respondents aged 18 and above. Structured questionnaires were used for data collection, and descriptive and inferential statistical analyses were performed using SPSS version 29.0. Key demographic characteristics such as age, education, and income were assessed, along with respondents' views on the impact of illegal immigration on service delivery, job competition, and cultural integration. Binomial logistic regression analysis was conducted to identify significant predictors of illegal immigration attitudes. The results reveal that age and education level are the strongest predictors of positive attitudes towards illegal immigration, while South African citizenship is associated with more negative perceptions. The findings highlight the complexity of public attitudes towards immigration, which are shaped by various demographic and socio-economic factors. Illegal immigration is perceived by some as a socio-economic factor contributing to crime and other illegal activities, although a significant portion of the population views it positively.